2015
DOI: 10.1111/aos.12917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early anatomical changes following canaloplasty with anterior segment spectral‐domain optical coherence tomography and ultrasound biomicroscopy

Abstract: ABSTRACT.Purpose: To analyse structural changes in conjunctiva, sclera and Schlemm's canal (SC) following canaloplasty with optical coherence tomography (AS-OCT) and ultrasound biomicroscopy (UBM). Methods: Fifteen patients undergoing canaloplasty were included in this prospective study. AS-OCT images were acquired pre-and 1, 7, 30 and 90 days postoperatively. UBM was performed 3 months postoperatively. The surgical site was evaluated for the presence of SC, transscleral filtration, a scleral lake and the visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…The explanation for this difference is likely the lower resolution of UBM compared to FD‐OCT, as reported by Fuest et al. ().…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The explanation for this difference is likely the lower resolution of UBM compared to FD‐OCT, as reported by Fuest et al. ().…”
Section: Discussionmentioning
confidence: 85%
“…These diameters are smaller than those acquired by FD-OCT in our study subjects. The explanation for this difference is likely the lower resolution of UBM compared to FD-OCT, as reported by Fuest et al (2016). One of the earliest published studies focusing on OCT measurements of cross-sectional SC area was that of Kagemann et al (2010) in adults, who reported values of 10 983 and 8308 lm 2 for the nasal and temporal quadrants, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to surgical treatments, AS OCT demonstrates an increase in SC size after canaloplasty in adults, correlating with a reduction in IOP. 32 Schlemm canal microstents are implanted in adults with open-angle glaucoma during cataract surgery 33,34 ; their possible usefulness in lensectomy in children is not known.…”
Section: Discussionmentioning
confidence: 99%